Electrospray synthesis of poly(lactide-co-glycolide) nanoparticles encapsulating peptides to enhance proliferation of antigen-specific CD8+ T cells - Kandil, Britta; Fricker, Gert (Journal of pharmaceutical sciences, 2017)
Polymer nanoparticles (NP) are of escalating interest for their application as immune stimulatory pharmaceutics. The production of nanosized carrier systems is currently being widely investigated, but commonly used techniques, such as the double emulsion technique, are limited by shortcomings of low encapsulation efficiency and poor control over size distribution. In this study, the electrospray technique was successfully implemented and optimized to produce monodisperse 200-nm poly(lactide-co-glycolide) (PLGA) NP. For cytomegalovirus (CMV) pp65 and IE-1 peptides, a consistent encapsulation efficiency of approximately 85% was achieved. In vitro stimulation of peripheral blood mononuclear cells (PBMCs) from CMV+ donors using electrosprayed pp65489-503 peptide-loaded NP revealed a significantly increased proliferation rate and frequency of antigen-specific CD8+ T cells as compared to the soluble peptide. The results of this study demonstrate the suitability of the electrospray technique for production of monodisperse PLGA NP with high drug encapsulation efficiency as promising peptide-based vaccine carriers.